Resistance to Multiple Tuber Diseases Expressed in Somaclonal Variants of the Potato Cultivar Russet Burbank - Tamilarasan Thangavel; Robert Steven Tegg; Calum Rae Wilson (The Scientific World Journal)
Multiple disease resistance is an aim of many plant breeding programs. Previously, novel somatic cell selection was used to generate potato variants of “Russet Burbank” with resistance to common scab caused by infection with an actinomycete pathogen. Coexpression of resistance to powdery scab caused by a protozoan pathogen was subsequently shown. This study sought to define whether this resistance was effective against additional potato tuber diseases, black scurf, and tuber soft rot induced by fungal and bacterial pathogens. Pot trials and in vitro assays with multiple pathogenic strains identified significant resistance to both tuber diseases across the potato variants examined; the best clone A380 showed 51% and 65% reductions in disease severity to tuber soft rot and black scurf, respectively, when compared with the parent line. The resistance appeared to be tuber specific as no enhanced resistance was recorded in stolons or stem material when challenged Rhizoctonia solani that induces stolon pruning and stem canker. The work presented here suggests that morphological characteristics associated with tuber resistance may be the predominant change that has resulted from the somaclonal cell selection process, potentially underpinning the demonstrated broad spectrum of resistance to tuber invading pathogens.